2008
DOI: 10.1111/j.1467-954x.2008.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

The Japanese Hikikomori Phenomenon: Acute Social Withdrawal among Young People

Abstract: Although rare in the west, in Japan and in some other advanced countries on the Asian-Pacific rim, there is a popular perception that there has been a significant increase in the numbers of young people who withdraw socially for protracted periods of time (referred to by the Japanese term 'hikikomori').This paper describes the hikikomori phenomenon in Japan, considers evidence relating to its prevalence and examines views about the causes. I argue that the tendency to think of hikikomori as a homogeneous group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
177
0
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(199 citation statements)
references
References 8 publications
8
177
0
14
Order By: Relevance
“…A less representative study by Lee et al (2013) suggested that 2.3% of high school students had been found to experience the state of social withdrawal in Korea. Nevertheless, cross-cultural studies are difficult to conduct, and reliable data for understanding youth social withdrawal and its impact on societies are scarce (Furlong, 2008). One of the major barriers to study this phenomenon is the heterogeneity of youth social withdrawal since youths can withdraw in different ways with different reasons, and there is no consensus on the definition or diagnostic criteria for youth social withdrawal in this field of study (Furlong, 2008;Lee et al, 2013;Wong, 2009).…”
Section: The Prevalence Of Youth Social Withdrawal Behaviormentioning
confidence: 99%
“…A less representative study by Lee et al (2013) suggested that 2.3% of high school students had been found to experience the state of social withdrawal in Korea. Nevertheless, cross-cultural studies are difficult to conduct, and reliable data for understanding youth social withdrawal and its impact on societies are scarce (Furlong, 2008). One of the major barriers to study this phenomenon is the heterogeneity of youth social withdrawal since youths can withdraw in different ways with different reasons, and there is no consensus on the definition or diagnostic criteria for youth social withdrawal in this field of study (Furlong, 2008;Lee et al, 2013;Wong, 2009).…”
Section: The Prevalence Of Youth Social Withdrawal Behaviormentioning
confidence: 99%
“…( Saito, 1998 ) Sociologists add that factors like Japan's economic destabilization and fundamental changes in the labor market resulting in irregular employment opportunities may also be a major contributor to the emergence of the phenomenon. ( Furlong, 2008 ) Disrupted family dynamics has also been attributed to the development of hikikomori. In a community study of the parents of 50 cases of hikikomori, family dynamics were assessed with the Family Asssessment Device (FAD).…”
Section: Psychopathologymentioning
confidence: 99%
“…Recently, a sociologic review of the topic appeared. ( Furlong, 2008 ) Nonetheless, hikikomori has never been reviewed by psychiatric or psychologist professionals in the English medical literature.…”
Section: History and Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…This pessimistic, unheroic withdrawal differentiates him from Astro Boy and other nuclear-powered commercial characters. However, the social and economic difficulties in the current society have led to an increase of NEETs-a person who is not pursuing employment, education, or training-and hikikomori, or extreme social withdrawal (Borovoy 2008;Furlong 2008). Monju-kun's desire to withdraw may have resonated with many young Japanese people.…”
mentioning
confidence: 99%